User grouping and power allocation algorithm for UAV-aided NOMA network - Guoquan LI; Jinzhao LIN; Yongjun XU; Zhengwen HUANG; Ting LIU (Tongxin xuebao, 2020)
To improve the transmission flexibility of emergency communication scenarios,a joint user grouping and power allocation algorithm was proposed for UAV-aided non-orthogonal multiple access (NOMA) system.A sum-rate maximization resource allocation algorithm was formulated under the constraints of the maximum transmit power and the user grouping.To solve the non-convex problem,a graph-based user grouping algorithm was proposed to minimize the relative distance between the UAV and users.Based on the grouping result,the power allocation sub-problem was transformed into a convex one by using the auxiliary-variable approach.Simulation results demonstrate that the proposed algorithm has better performance in terms of sum rates.